African Literature and US Empire - Hallemeier, Katherine (Edinburgh University Press, 2024)
Postcolonialism has long been associated with post-nationalism. Yet, the persistence of nation-oriented literatures from within the African postcolony and its diasporas registers how dreams of national becoming endure. In this fascinating new study, Hallemeier brings together African literary studies, affect studies and US empire studies, to challenge chronologies that chart a growing disillusionment with the postcolonial nation and national development across the twentieth and twenty-first centuries. The Nigerian and South African writings in African Literature and US Empire, while often attuned to the trans- and extra- national, repeatedly scrutinise why visions of national exceptionalism, signified by a ‘pan-African’ Nigeria and ‘new’ South Africa, remain stubbornly affecting, despite decades of disillusionment with national governments beholden to a neocolonial global order. In these fictions, optimistic forms of nationalism cannot be reduced to easily critiqued state-sanctioned discourses of renewal and development. They are also circulated through experiences of embodied need, quotidian aspiration and transnational, pan-African relationship.